PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS IV SEKOLAH DASAR NEGERI SADE BARABALI LOMBOK TENGAH - Yuliani, Meri; Habibi, Muhamad Ridwan; Murnihati , Susila Sri; Majid , Abdurrrahman (LPPM Institut Pendidikan Nusantara Global, 2022)
Background of this research problem is the low activity of student learning in Thematic learning in class IV SDN Sade Barabali Lombok Tengah that caused by the low quality of learning that used by teacher, where the lack of methods, models and strategies that used by the teacher during the process of thematic learning led to boredom on students and become passive during the learning process. This research is a Classroom Action Research (PTK) with qualitative descriptive method that using a qualitative approach reinforced by quantitative approach, by talking the background in SDN Sade Barabali Lombok Tengah, The subject of this research is the fourth grade students in SDN Sade Barabali Lombok Tengah, while the object of this research is the Application of The Teams Games Tournament Learning Models to Increase The Learning Activity in Cita-Citaku theme. This research was conducted in two cycles and through 4 stages including: (1) Planning, (2) Implementation, (3) Observation and (4) Reflection. The data obtained through observation, interviews, and documentation. Data analysis is done by using qualitative analysis that consist of data collection, data reduction, data presentation, conclusion of verification. The result of this research indicates that the application of models Teams Games Tournament can increase students learning activity in learning process. Activity can be measured from the evaluation cycle I, and cycle II of 63% and 77,5% cycle II. While the improvement of student activity can be measured from each cycle, student activity in cycle I is 3,1 with the active approaching category and student activity in cycle 4,1 with the approaching very active category. Thus the result of this research in Dasar Negeri School Sade Barabali Lombok Tengah has been achieved with good.